SATISFACTION AND REVISITING INTENTION OF TOURISM TOWARDS BEACH TOURISM IN TAMIL NADU (CAHIERS MAGELLANES-NS, 2024)
Tourism boosts the profit of the frugality, makes thousands of careers, grows the architecture of a republic, and plants a sense of artistic exchange between innovative and peoples. The quantity of jobs created by travel in numerous different areas is significant. strands along the seacoast give multitudinous recreational openings for millions of people. voyaging, fumbling, swimming, walking, and sunbathing are among the multitudinous conditioning enjoyed by beachgoers. strands give unique territories for a variety of shops and creatures. Coastal areas are frequently cooler than places inland. So, on hot days people go to the sand to cool off and plunge in the marine. numerous persons enjoy calming down on the sand. In the once sunbathing was veritably popular, although moment excursionists are more apprehensive of the troubles of too important sun. strands are lucrative as well as natural coffers. As natural coffers, they add beauty to the seacoast and give territories to numerous brutes including catcalls and ocean turtles. As profitable coffers, they give services to people and property that have a profitable value. The main end of the study is the evolution and progress of sand tourism in Tamil Nadu. To fete the beach tourism and the position of the sightseer for reconsidering the destination and understand and linked the factors stations to reconsidering intention of sand destination in Tamil Nadu.